Ingested house dust mite favors sensitization to egg white in mice independently of its proteinase activity - Benedé, Sara; Pérez-Rodríguez, Leticia; Menchén-Martínez, David; Molina, Elena; López-Fandiño, Rosina (Frontiers in Immunology, 2025)
BackgroundIt is well-documented that house dust mite (HDM) exposure can cause tissue damage and activate innate immune responses. However, its role in promoting gastrointestinal sensitization and allergenicity to food proteins has been relatively unexplored.MethodsThis study investigates the immunostimulatory effects of HDM in a murine model of oral sensitization to egg white (EW) in the absence of exogenous adjuvants. Additionally, we examined a proteolytically inactivated form of HDM (iHDM) to assess the contribution of HDM protease activity to its adjuvant potential.ResultsBoth HDM and iHDM enhanced allergic responses to EW proteins via the oral route, evidenced by mast cell degranulation in the intestinal tract upon EW challenge. Notably, only iHDM induced detectable concentrations of serum EW-specific IgE and IgG1 antibodies. Whereas HDM increased intestinal expression of genes encoding tight junction proteins and Th2-inducing alarmins to a greater extent than iHDM, active proteinases were not required for its adjuvant activity, as iHDM preferentially promoted Th2 responses in intestinal lymphoid tissues.ConclusionsThese findings suggest that ingestion of environmental dust may contribute to food allergy development and highlight the complex and context-dependent nature of the adjuvant activity of HDM.